O recurso cênico teatral como instrumento de ensino-aprendizagem quanto à organização de textos narrativos na escola pública - Gusmão Júnior, Ediney (2009)
The aim of this research is to investigate and comprehend the teathral scenic instrument, specificly, the dramatic game in the class room context, to the criacion of the contexts that do learning and development of the public school students as for the narratives oral texts production. The activity focus has a propose to be a pedagogical intervencion in the teaching routine of a public school. This study is grounded on the sócio-historicalcultural activity theory (VYGOTSKY, 1930/1999, 1930/2000, 1931/1995, 1987, 1934/2001; LEONTIEV, 1977; ENGSTRÖM, 1987), on the vygotskyan conception of criativity (VYGOTSKY, 1930/1999, 1930/2000), and on the concept of dialogism and verbal interaction (BAKHTIN, 1970/2000; BAKHTIN/VOLOCHINOV, 1929/2002), on the system turn (KERBRAT-ORECCHIONI, 1996/2006), on the argumentaction (PERELMAN & OLBRECHTS, 1996; ABREU, 2007). It is supported too on the subjects that discuss the teathral theory (COURTNEY, 1968/1980; SPOLIN, 1963/1979; SLADE, 1978). These theories allowed comprehend the way that the dramatic games can do a criative interaction and the nature collaboration that occur in this place, how too, to watch the rules took by the participants in the argued object construction. This is a critical research collaboration (MAGALHÃES, 1994, 1996, 1998ª, 1998b, 1998c, 2002, 2003ª, 2003b; LIBERALI, 1994, 1999, 2007b), as a participant on the teacher place and researcher wanted conduct, analyse and comprehender and help to the tranformations by means of taking object concepts on study, helping on students development. The analysis of the selected data focused their contexto of production, theme contents, general text plain, analysis of turn taking and argumentation in order to comprehend if the dramatic game in the class room context can fulfills this aim. The results show that the dramatic game were constituted as a instrument to taking to the students concepts to narrative, because the colaborative set that the activity give, put them to live imaginary situactions, in that they could developed of the real world representactions, as the oral language organization and the narrative organization